THE ROLE OF CHILDREN TO PARENTS A PERSPECTIVE FROM THE QURAN SURAH AL ISRA, VERSES 23-24 - Zazuli, Ahmad; Maula, Ainussyifaul; Fathimah, Ajeng Dewi; Wicaksono, Aji Hanif; Febriani, Evi (Program Studi Pendidikan Agama Islam, 2025)
This article discusses the role of children towards parents from the perspective of the Qur'an, especially based on Surah Al-Isra, verses 23-24. In this verse, Allah SWT commands humans to worship only Him and to be kind to both parents with respect and affection. Children are required not to say harsh words such as